Design of unknown input fractional-order observers for fractional-order systems - N`Doye, Ibrahima; Darouach, Mohamed; Voos, Holger; Zasadzinski, Michel (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers a method of designing fractional-order observers for continuous-time linear fractional-order systems with unknown inputs. Conditions for the existence of these observers are given. A stability analysis of the fractional-order error system is made and it is shown that the fractional-order observers are as stable as their integer order counterpart and guarantee better convergence of the estimation error.
Keywords: fractional calculus; fractional-order systems; fractional-order observers; existence condition; linear matrix inequality; unknown inputs; stability